2013
DOI: 10.1007/s13311-013-0206-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms of Neurodegeneration in Huntington's Disease

Abstract: Huntington's disease (HD) is an incurable and fatal hereditary neurodegenerative disorder of mid-life onset characterized by chorea, emotional distress, and progressive cognitive decline. HD is caused by an expansion of CAG repeats coding for glutamine (Q) in exon 1 of the huntingtin gene. Recent studies suggest that epigenetic modifications may play a key role in HD pathogenesis. Alterations of the epigenetic "histone code" lead to chromatin remodeling and deregulation of neuronal gene transcription that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 124 publications
(176 reference statements)
0
63
0
Order By: Relevance
“…Epigenetic modification is involved in the regulation of large number of genes regulation, and it has been suggested that the microRNAs, DNA methylation of specific gene promoters and histone modifications (acetylation, phosphorylation and methylation) are regarded as the most popular epigenetic genes [51,52]. Furthermore, a growing body of recent publications indicate that epigenetics plays a crucial role in controlling HIF-1a activity [53,54].…”
Section: Epigenetics/hif-1a Network Signaling Pathwaymentioning
confidence: 99%
“…Epigenetic modification is involved in the regulation of large number of genes regulation, and it has been suggested that the microRNAs, DNA methylation of specific gene promoters and histone modifications (acetylation, phosphorylation and methylation) are regarded as the most popular epigenetic genes [51,52]. Furthermore, a growing body of recent publications indicate that epigenetics plays a crucial role in controlling HIF-1a activity [53,54].…”
Section: Epigenetics/hif-1a Network Signaling Pathwaymentioning
confidence: 99%
“…On the other hand, the huntingtin protein has been shown to have a significant impact on many epigenetic marks, ranging from various histone modifications to DNA methylation [36-38]. Aberrant DNA methylation has also been reported both downstream and upstream of the expansion in frataxin [39], with hypermethylation especially in the first intron showing a direct correlation with the expansion size and the age of onset [40].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic changes are also determinant in several neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease or Huntington's disease [9,15,16,31,32]. …”
Section: Brain Disordersmentioning
confidence: 99%
“…In Western countries, AD is the most prevalent form of dementia (45-60%), followed by vascular dementia (VD) (30-40%), and mixed dementia (10-20%), which in people older than 85 years of age may account for over 80% of the cases. The different forms of dementia pose several challenges to our society and the scientific community: (i) they represent an epidemiological problem, and a socio-economic, psychological and family burden; (ii) most of them have an obscure/ complex pathogenesis; (iii) their diagnosis is not easy and lacks specific biomarkers; and (iv) their treatment is difficult and inefficient [2,3,31,34,35]. In terms of economic burden, approximately 10-20% of direct costs are associated with pharmacological treatment, with a gradual increase in parallel with the severity of the disease.…”
Section: Alzheimer's Diseasementioning
confidence: 99%